Análisis de Confiabilidad en Subestaciones Eléctricas Tipo Maniobra Implementando el Transformador de Tensión con Núcleo de Potencia - Viteri, Diego Ernesto; Garzón Bustos, César Andrés; Narvaez Cubillos, Eider Alexander (Ingeniería, 2017)
Context: It is intended to conduct a technical study of a voltage transformer power core, used for the supply of the auxiliary services of a maneuver type substation, hoping to mitigate the possibility of losing the continuous electricity power supply and likewise reducing the dependency with the external supplier. This is a result of a collaborative project between the Bogota Energy Company and the Universidad Distrital Francisco Jose de Caldas. Method: The study consists of two stages, the first one is an analysis of reliability of the substation auxiliary systems, carried out in three scenarios: before and after use of the transformer and using a unique generator for auxiliary services. The second one is simulation using the ATP software to verify the behavior of the equipment in transient state. Results: The reliability of auxiliary services increased after the equipment has been installed, as the failure rate went from 0.31 [failure/year] with the current system, to become 0.0025 [failure/year]. Conclusions: The implementation of transformer is suitable for substations that do not have a reliable power system auxiliary services as it makes the substation auto dependent. Implement this system in Colombia would get a big increase in the reliability of the auxiliary services in maneuver type substations and therefore a lower probability of loss.